Ultrasmall CuCo2S4 Nanocrystals: All‐in‐One Theragnosis Nanoplatform with Magnetic Resonance/Near‐Infrared Imaging for Efficiently Photothermal Therapy of Tumors. (23rd January 2017) - Li, Bo; Yuan, Fukang; He, Guanjie; Han, Xiaoyu; Wang, Xin; Qin, Jinbao; Guo, Zheng Xiao; Lu, Xinwu; Wang, Qian; Parkin, Ivan P.; Wu, Chengtie
Abstract : Copper‐based ternary bimetal chalcogenides have very promising potential as multifunctional theragnosis nanoplatform for photothermal treatment of tumors. However, the design and synthesis of such an effective platform remains challenging. In this study, hydrophilic CuCo2 S4 nanocrystals (NCs) with a desirable size of ≈10 nm are synthesized by a simple one‐pot hydrothermal route. The as‐prepared ultrasmall CuCo2 S4 NCs show: 1) intense near‐infrared absorption, which is attributed to 3d electronic transitions from the valence band to an intermediate band, as identified by density functional theory calculations; 2) high photothermal performance with a photothermal conversion efficiency up to 73.4%; and 3) capability for magnetic resonance (MR) imaging, as a result of the unpaired 3d electrons of cobalt. Finally, it is demonstrated that the CuCo2 S4 NCs are a promising "all‐in‐one" photothermal theragnosis nanoplatform for photothermal cancer therapy under the irradiation of a 915 nm laser at a safe power density of 0.5 W cm −2, guided by MR and infrared thermal imaging. This work further promotes the potential applications of ternary bimetal chalcogenides for photothermal theragnosis therapy. Abstract : Ultrasmall CuCo2 S4 nanocrystals are developed as an efficient photothermal theragnosis agent. The nanocrystals exhibit intense near‐infrared absorption attributed to 3d electronic transitions from the valence band to an intermediate band, as identified by density functional theory calculations, and capability for magnetic resonance imaging, as a result of the unpaired 3d electrons of cobalt.